Education, Religion, and Social Transformation: The Role of Schools in Fostering Civic Engagement and Ethical Leadership - Hayaturraiyan Hayaturraiyan; Muhammad Roil (Institut Studi Islam Muhammadiyah Pacitan, 2026)
This study examines the role of education in fostering civic engagement and ethical leadership as key components of social transformation, particularly through the integration of religious and moral values within school systems. Using a qualitative, literature-based approach, the study analyzes recent scholarly works to explore how schools function as transformative institutions. The findings reveal that the integration of civic education, character education, and religious values significantly contributes to students’ moral development, social responsibility, and active participation in society. Participatory learning, community involvement, and ethical leadership practices within schools further strengthen students’ civic competencies and leadership capacities. In the Indonesian context, the incorporation of Islamic values such as justice, trustworthiness, and social solidarity enhances ethical awareness and civic consciousness. However, challenges such as limited teacher training and rigid curricula remain barriers. The study concludes that holistic and value-based educational approaches are essential for developing ethically responsible and civically engaged citizens.